Effect of Recreation on Self-esteem: A Meta-analysis - Romero-Barquero, Cecilia Enith (2024)
Objective. This meta-analysis (MA) aimed to assess the effectiveness of recreation on self-esteem and to analyze possible moderating variables. Method. Fifty-five studies were included, with 3782 participants, and 117 effect sizes (ES). The analyses comprised within-groups design, the random effects model, the Q statistic and inconsistency with the I2. Results. It was found that the ES of the experimental group was moderate, positive and significant (ES = .70). Recreational programs significantly improved self-esteem. In addition, the type of leadership of the activity, the type of recreational activity and the condition of the sample were variables that significantly moderated the ES of self-esteem. It is recommended to offer recreational activities to people from the ages of 9.5 to 79.